DEPRECIATION–THE DEVELOPMENT OF AN ACCOUNTING CONCEPT. - Woodward, P. D. (The Accounting Review, 1956)
Abstract To many accountants depreciation as we know it today represents an idea which is a generally accepted accounting principle. Business has not always had such respect for depreciation accounting. This article has as its goal a highlight review of some of the interesting changes, which have occurred in the development of this accounting concept. The idea of depreciation was not clearly established by the latter part of the nineteenth century. In 1876, the United States Supreme Court stated, in referring to the determination of the profit of a merchant, that it was unusual to take into account depreciation on a building in which a merchant maintained his business. In 1878, the United States Supreme Court criticized the practice of establishing depreciation reserves through periodic charges to operating expense, and held that only the actual expenses of renewals could be charged to operating expense. The idea as expressed by the Supreme Court was apparently the common thinking of business leaders, for the Third National Convention of Railroad Commissioners in 1879 adopted a report on uniform accounts which included the following instruction no expenditure is chargeable for an actual increase though unless it is made on old work in such a way as to clearly increase the value of the property over and above the cost of renewing the original structures. Corollary to this idea was the thought that if property were properly maintained there would be no depreciation.